2021
DOI: 10.3390/jof7040310
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Species Diversity of Edible Mushrooms in Yunnan, Southwestern China, by DNA Barcoding

Abstract: Yunnan Province, China, is famous for its abundant wild edible mushroom diversity and a rich source of the world’s wild mushroom trade markets. However, much remains unknown about the diversity of edible mushrooms, including the number of wild edible mushroom species and their distributions. In this study, we collected and analyzed 3585 mushroom samples from wild mushroom markets in 35 counties across Yunnan Province from 2010 to 2019. Among these samples, we successfully obtained the DNA barcode sequences fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 90 publications
0
27
0
Order By: Relevance
“…in the country [57,58]. Russula is apparently among the most valuable traded edible fungi in China [59] and also in Himalayan regions of Northern India and Nepal, but they are usually members of subgenera Heterophyllidiae Romagn. and Brevipedum Buyck and V. Hofst.…”
Section: Discussionmentioning
confidence: 99%
“…in the country [57,58]. Russula is apparently among the most valuable traded edible fungi in China [59] and also in Himalayan regions of Northern India and Nepal, but they are usually members of subgenera Heterophyllidiae Romagn. and Brevipedum Buyck and V. Hofst.…”
Section: Discussionmentioning
confidence: 99%
“…This study analyzed 96 samples using sequence information at both the tef-1 locus and the internal transcribed spacer (ITS) regions of the ribosomal RNA gene cluster. However, a very conservative cutoff for species delimitation was used in new species estimation in this study (Zhang et al, 2021). Another study identified that most of the edible yellow chanterelles old in the Yunnan local markets belonged to C. Yunnanensis based on both morphological and tef-1sequences, and not the traditionally assumed C. cibarius (Shao et al, 2021).…”
Section: Introductionmentioning
confidence: 90%
“…Because of the relatively high heterogeneity of the primary fungal DNA barcode ITS within individual samples of C. cibarius and related species, high quality ITS sequences are often not available for species identification within this species complex (Buyck et al, 2020;Zhang et al, 2021). Instead, as in previous studies , the tef-1 gene was used as the DNA barcode to determine the taxonomic placements of our Cantharellus specimens.…”
Section: Species Identificationmentioning
confidence: 99%
See 2 more Smart Citations